SYLVA’S MARI PEOPLE: THE RATIO OF ETHNIC AND REGIONAL IDENTITY - Ivanova, M.V. (Perm Federal Research Centre Journal, 2015)
The article presents the results of the research, which was carried out in three villages of the Suksun region of Perm Krai: Vaskino, Ivankovo, Tebenyaki. These settlements are densely inhabited by the Mari, who are distinguished by ethnographers as a separate group of the Sylva’s Mari people on the basis of historically developed differences in mentality, culture, customs, ceremonies, national clothes, and language. The object of this research is to find out the importance of ethnic and regional factors for the Sylva’s Mari people, and to characterize the features of self-identification by the habitants of these villages.